Inhibition of Zinc Dendrites in Zinc-Based Flow Batteries - Guo, Leibin; Guo, Hui; Huang, Haili; Tao, Shuo; Cheng, Yuanhui (Frontiers in Chemistry, 2020)
Zinc-based flow batteries have gained wide attention and are considered to be one of the most promising large-scale energy storage devices to increase the utilization of intermittently sustainable energy. However, the formation of zinc dendrites at anodes has seriously depressed their cycling life, security, coulombic efficiency, and charging capacity. So inhibition of zinc dendrites is the bottleneck to further improve the performance of zinc-based flow batteries but remains a big challenge. Considering recent developments, this mini-review analyzes the formation mechanism and growth process of zinc dendrites, presents and summarizes the strategies to prevent zinc dendrites by regulating the interfaces between anodes and electrolytes. Four typical strategies in terms of electrolyte modification, anode engineering, electric field regulation, and ions transfer control are comprehensively highlighted. Finally, remaining challenges and promising directions are outlined and expected for zinc dendrites in zinc-based flow batteries.